Production of xylo-oligosaccharides by different treatments of banana pseudostem and their prebiotic evaluation via probiotic bacteria growth and their metabolites - Freitas, Caroline de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Xylooligosaccharides (XOS) are oligomers from xylan, a hemicellulose found in many types of plants. Their structure is composed of xylose units linked through β-1,4 bonds, which makes them non-digestible by the human digestive system but fermentable by probiotic microorganisms present in the gut flora. XOS can be produced by acid or enzymatic hydrolysis of biomass from agro-industrial residues, such as banana pseudostem, or from solubilized xylan from these residues. In this context, this study compared the production of XOS by these different methods, analyzed the xylan structure after hydrolysis, and the tolerance of probiotic microorganisms by compounds used and produced in the acid hydrolysis process. After that, the growth of the microorganisms was evaluated in the presence of different concentrations of XOS and the metabolites produced by its fermentation. In the enzymatic hydrolysis of biomass, using both strategies of partial delignification and milling, the XOS yield went up by 47% compared to the biomass that has not gone through these two processes. In addition, the xylan molecular weight analyzed after two hydrolysis cycles indicate that the remaining complex substrate limited enzyme action. The production of XOS by diluted acid hydrolysis of banana pseudostem biomass is also an alternative since the conversion was good and there was low production of xylose and sugar degradation by-products. Probiotic bacteria growth was influenced by organic acids, furfural, and HMF in different concentrations, also by the consequent pH of the medium. The higher the concentration of these compounds, the lower the Lactobacillus growth, however, the bifidobacteria used in this study were more resistant. Concentrations of acetic, lactic, and formic acid increase, in some cases, after bifidobacteria growth, indicating that they also produce these organic acids. Generally, the higher the concentration of furfural and HMF, lower the growth. For Lactobacillus, concentrations of 10, 7.5 and 5 g/L HMF and 10 g/L furfural inhibited growth. All tested microorganisms grew when cultured using XOS produced via acid hydrolysis as their carbon source. For most microorganisms, the optimal XOS concentration for growth was 20 g/L fermentation. Concentrations of metabolites produced varied depending on the carbon source and microorganism used, however, lactate and acetate were the most produced.

Xilo-oligossacarídeos (XOS) são oligômeros derivados da xilana, uma hemicelulose encontrada em muitos tipos de plantas. Sua estrutura é composta por unidades de xilose ligadas por ligações β-1,4, tornando-os não digeríveis pelo sistema digestivo humano, mas fermentáveis por microrganismos probióticos presentes na flora intestinal. Os XOS podem ser produzidos por hidrólise ácida ou enzimática de biomassa proveniente de resíduos agroindustriais, como pseudocaule de banana, ou de xilana solubilizada desses resíduos. Nesse contexto, este estudo comparou a produção de XOS por esses diferentes métodos, analisou a estrutura da xilana após a hidrólise e a tolerância de microrganismos probióticos aos compostos utilizados e produzidos no processo de hidrólise ácida. Em seguida, o crescimento dos microrganismos foi avaliado na presença de diferentes concentrações de XOS e dos metabólitos produzidos por sua fermentação. Na hidrólise enzimática da biomassa, utilizando estratégias de deslignificação parcial e moagem, o rendimento de XOS aumentou em 47% em comparação com a biomassa que não passou por esses dois processos. Além disso, o peso molecular da xilana analisado após dois ciclos de hidrólise indica que o substrato complexo restante limitou a ação da enzima. A produção de XOS por hidrólise ácida diluída da biomassa do pseudocaule de banana também é uma alternativa, uma vez que a conversão foi boa e houve baixa produção de xilose e subprodutos de degradação do açúcar. O crescimento de bactérias probióticas foi influenciado por ácidos orgânicos, furfural e HMF em diferentes concentrações, também pelo pH resultante do meio. Quanto maior a concentração desses compostos, menor o crescimento de Lactobacillus; no entanto, as bifidobactérias utilizadas neste estudo foram mais resistentes. Concentrações de ácido acético, láctico e fórmico aumentaram, em alguns casos, após o crescimento das bifidobactérias, indicando que também produzem esses ácidos orgânicos. Geralmente, quanto maior a concentração de furfural e HMF, menor o crescimento. Para o Lactobacillus, concentrações de 10, 7,5 e 5 g/L de HMF e 10 g/L de furfural inibiram o crescimento. Todos os microrganismos testados cresceram quando cultivados usando XOS produzidos por hidrólise ácida como fonte de carbono. Para a maioria dos microrganismos, a concentração ótima de XOS para o crescimento foi de 20 g/L de fermentação. As concentrações de metabólitos produzidos variaram dependendo da fonte de carbono e do microrganismo utilizado; no entanto, o lactato e o acetato foram os mais produzidos.
Produção de xilo-oligossacarídeos por diferentes tratamentos do pseudocaule da bananeira e sua avaliação prebiótica através do crescimento de bactérias probióticas e seus metabólitos.
Keywords: Xylooligosaccharides; Endoxylanase; Organic acids; Prebiotics; Probiotics; By-products; Xilo-oligossacarídeos; Endoxilanase; Ácidos orgânicos; Prebióticos; Probióticos; Sub-produtos